What Do We Know About Chain Actors' Evaluation of New Food Technologies? A Systematic Review of Consumer and Farmer Studies. Issue 3 (15th April 2019) - Kamrath, Carolin; Wesana, Joshua; Bröring, Stefanie; De Steur, Hans
Abstract: New food technologies, such as genetic modification, food fortification, and processing technologies, are of growing interest for future food security and safety. For ensuring successful implementation of such technologies, consumers and other food supply chain actors should embrace them. We present a systematic review to identify and compare key factors of supply chain actors' evaluation of new food technologies. Evaluation encompasses indicators such as likelihood or intention to perform a behavior, perceived benefits/risks, willingness to pay, acceptance/adoption, and attitudes. Results from 183 studies showed several imbalances in research. Although studies mainly focused on (1) genetically modified foods, (2) by consumers, (3) in developed countries, only very few studies have targeted other food technologies, other supply chain actors such as farmers (13 studies) or processors (two studies), or developing countries (43 studies). With respect to consumers' evaluation, key determinants were trust in institutions, information assessment, perceived risks and benefits, attitudes toward the product or technology, perceived behavioral control, quality perception of the product, and impact on health. Farmers' evaluation of new food technologies was explained by the factors of perceived risk and benefits and of actual source of information. For the few processor evaluation studies, no convergence of factors could be reached. This systematic review contributes to a better understanding of consumers' and farmers' evaluation behavior and opens up avenues for future research on supply chain actors' food technology evaluations. The differences in the conceptualization and measurement of extracted factors demonstrate the need for standardized approaches in future studies.